Improving health professionals’ capacity to respond to the climate crisis in Africa: outcomes of the Africa climate and health responder course - Magalhães, Danielly de P.; Sorensen, Cecilia; Hamacher, Nicola; Campbell, Haley; Weinstein, Hannah N. W.; Owili, Patrick O.; Ario, Alex R.; Nja, Glory M. E.; Michael, Charles A.; Alimi, Yewande; Hien, Hervé; Amde, Woldekidan; et al. (Frontiers in Public Health, 2025)
IntroductionThe fragile health systems in Africa worsen climate-related health impacts, making capacity building essential to strengthen adaptation and resilience. The Africa Climate and Health Responders Course was developed to address the urgent need for climate and health education among African health professionals. Organized by the Global Consortium on Climate and Health Education (GCCHE) in collaboration with ASPHA, Africa CDC, WHO AFRO, Project ECHO, and other regional partners, the course aimed to enhance awareness, communication skills, and preparedness in responding to climate-related health challenges.MethodsDelivered online via Zoom with over 11 sessions (September 17–October 22, 2024), the course featured expert lectures, case studies, and live discussions. Simultaneous interpretation in English, French, and Portuguese ensured broad accessibility. Participants who attended at least 70% of live sessions and passed the final exam received a certificate. A longitudinal survey was applied to understand the course impact.ResultsThe course attracted 7,572 registrants, with 89% from Africa. While 3,500 participants attended at least one session, only 1,657 participated (1,607 from Africa) attended 70% or more of the sessions and completed the final survey. Participants held positions in government (31%), Non-Governmental Organizations (NGOs) (27%), academia (24%), private sector (11%), and others (7%). Their main professional backgrounds were public health (33.2%), medicine (16.3%), and environmental health (13.2%). The majority of participants (66%, n = 1,100) had never received prior training in climate and health; among them, 36% (n = 392) were students and 64% (n = 708) were not students.DiscussionThe course significantly improved participants’ self-reported confidence and perceived preparedness, with increases in: climate-health awareness (+22%); confidence in risk communication (+40%); preparedness for adaptation and resilience (+36-37%), and professional responsibility in climate-health action (+21%). These findings highlight not only the feasibility and effectiveness of virtual training in this context, but also the opportunity for scaling such initiatives to build a climate-resilient health workforce across Africa. Skilled professionals are key to fostering multi-stakeholder collaboration, integrating climate-health education, and engaging communities—efforts that require sustained investment in capacity building to institutionalize competencies and strengthen public health systems and policies over the long term.